Students’ Perceptions of English Speaking Learning in Online and Offline Classes: A Case Study of Intensive Course Class - Sulis Dangkua; Nonny Basalama; Muziatun (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This study explores students’ perceptions of English speaking learning in online and offline classes, focusing on the Intensive Course class at Gorontalo State University. Employing a qualitative approach, data were collected through closed-ended questionnaires and documentation of students’ GPA in speaking-related courses. The participants were students from the 2021 cohort (online learning) and 2022 cohort (offline learning). The study examined seven key components of speaking skills: fluency, pronunciation, grammar, vocabulary, comprehension, confidence, and engagement. The results indicate that students who experienced offline learning reported more positive perceptions across almost all components, attributing their improvement to real-time interaction, direct feedback, and active class participation. Meanwhile, students in online learning perceived improvement particularly in pronunciation and fluency, supported by independent practice and flexible access to digital resources, yet faced challenges in engagement and interaction. Despite these perception differences, the average GPA between the two groups was relatively similar. The findings, interpreted through Vygotsky’s Sociocultural Theory, highlight the importance of social interaction and scaffolding in speaking skill development. Overall, offline learning was perceived as more effective in fostering speaking competence.